1987
DOI: 10.1007/bf00586515
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-activated potassium, but not calcium currents in cultured bovine aortic endothelial cells

Abstract: The electrophysiological properties of cultured bovine aortic endothelial cells were characterized using the patch clamp technique. Resting potentials were measured on passing to the whole cell recording configuration and were close to--65 mV in healthy cells. In cell-attached recordings with a high potassium pipette solution, inward single channel currents were observed with zero applied pipette potential. A linear slope conductance of 25 pS was found for a wide range of hyperpolarizing patch potentials and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 57 publications
9
69
0
Order By: Relevance
“…The conductance of 17 pS is within the range of typical values for inward rectifier channels, and similar to that shown in endothelial cells (e.g. Takeda et al 1987;Hoyer et al 1991). …”
Section: Non-selective Cation Channelssupporting
confidence: 84%
See 1 more Smart Citation
“…The conductance of 17 pS is within the range of typical values for inward rectifier channels, and similar to that shown in endothelial cells (e.g. Takeda et al 1987;Hoyer et al 1991). …”
Section: Non-selective Cation Channelssupporting
confidence: 84%
“…IDR was initially described in skeletal muscle and cardiac cells, and was later found in tunicate eggs and neurons (reviewed in Hille, 1992), as well as in cultured (Takeda et al 1987) and freshly dissociated (Hoyer et al 1991) endothelial cells. IIR is not regarded as a current typical for smooth muscle cells, and has so far only been described in smooth muscle from small arteries and arterioles in the cerebral and coronary circulations (Quayle et al 1993(Quayle et al , 1997Johnson et al 1998), although a low density of IIR has recently been reported in small renal arteries (Prior et al 1998).…”
Section: Non-selective Cation Channelsmentioning
confidence: 99%
“…Firstly, the measured membrane potential was lower than that recently found by use of similar techniques in cultured bovine arterial endothelial cells (Takeda et al, 1987;Colden-Stanfield et al, 1987;Adams et al, 1987;Johns et al, 1987). However, similar low values of resting potentials have been reported in confluent endothelial cell cultures (Venter et al, 1975;Richter & Halle, 1983) and in intact tissue (Northover, 1980), where gap junctions and electrical coupling between cells can be expected to be present (Simionescu et al, 1975;Venter et al, 1975).…”
Section: Discussionmentioning
confidence: 53%
“…Experimental methods, data recording on FM tape (Bruel & Kjaer, Denmark) and offline computer (Labtam, Australia) analysis procedures are similar to those previously described elsewhere in detail (Bregestovski et al, 1986;Takeda et al, 1987). Pipettes for whole cell recording had resistances of 3-7 MO.…”
Section: Electrophysiologymentioning
confidence: 99%
“…These findings suggest that the agonist-induced increase in transmembrane Ca2+ influx was much larger in aortic than in coronary endothelial cells. This conclusion is supported by spectrofluorometric (Indo-1) (Takeda, Schini & Stoeckel, 1987) with a negative slope between -50 and -25 mV (Cannell & Sage, 1989 (Daut et al 1988). The molecular mechanism underlying the negative slope of the current-voltage relation in BAECs may be a decrease in the open probability of the inwardly rectifying K+ channel with depolarization, as has been found in cardiac ventricular muscle (Kurachi, 1985).…”
Section: Discussionmentioning
confidence: 63%